2012
DOI: 10.1148/radiol.12111177
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Breast Cancer: Prediction of Pathologic Response with PET/CT and Dynamic Contrast-enhanced MR Imaging—Prospective Assessment

Abstract: The sensitivities of %SUV(max) (66.7%), %k(ep) (51.7%), and %AUC(90) (50.0%) at (18)F-FDG PET/CT and DCE MR after two cycles of NAC are not acceptable, but the specificities (96.4%, 92.0%, and 95.2%, respectively) are high for stratification of pCR cases in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 25 publications
4
79
3
Order By: Relevance
“…Our results contradict those of the only other study to date comparing the performance of DSUV max and DTLG-a study that reported a higher predictive value for DSUV max (13). In that previous study, DSUV mean , DSUV peak , and DMATV predictive values were not considered.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results contradict those of the only other study to date comparing the performance of DSUV max and DTLG-a study that reported a higher predictive value for DSUV max (13). In that previous study, DSUV mean , DSUV peak , and DMATV predictive values were not considered.…”
Section: Discussioncontrasting
confidence: 99%
“…These parameters, which allow for a more comprehensive tumor functional level evaluation, include metabolically active tumor volume (MATV) (11) and total lesion glycolysis (TLG), defined as the product of MATV and its associated SUV mean (12). In a recent study that compared SUV max and TLG derived using manual delineation and threshold, SUV max had a better predictive value than TLG in identifying pCR (13).…”
mentioning
confidence: 99%
“…33 In addition, all cancer subtypes were mixed (ERþ/HER2À, triple-negative, and HER2-positive), and the endpoint was to predict pCR. 32 The higher predictive value of DTLG over DSUV max that we observed in these ERþ/HER2À tumors may have several explanations. Baseline 18 F-FDG uptake is weaker and the decrease in SUV during NAC is lower than for other phenotypes, 8,10,13 as demonstrated in 1 study (À45% AE 25% and À57% AE 30%, respectively, in the TN and HER2-positive subtypes versus À19% AE 35% in the ERþ/HER2À subtype; P < .0001).…”
Section: Discussionmentioning
confidence: 78%
“…In many studies [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] that have evaluated a possible role for metabolic evaluation with FDG-PET and PET/ CT, investigators demonstrated a correlation between early changes in FDG uptake, mostly in terms of the SUV max value, after one or two courses of chemotherapy and the final pathologic response upon completion of chemotherapy, or patient outcome (Table 4). A review article including 745 patients in 15 studies indicated that the pooled sensitivity and specificity of FDG-PET for early separation of responders from non-responders could reach 80.5 % (95 % CI, 75.9-84.5 %) and 78.8 % (95 % CI, 74.1-83.0 %), respectively [91].…”
Section: Early Treatment Response Assessmentmentioning
confidence: 99%